2008
DOI: 10.1212/01.wnl.0000306632.43729.24
|View full text |Cite
|
Sign up to set email alerts
|

Dementia and survival in Parkinson disease

Abstract: Dementia is a key part of survival in Parkinson disease and must be planned for in services for this condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
243
4
9

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 412 publications
(263 citation statements)
references
References 36 publications
7
243
4
9
Order By: Relevance
“…Its incidence increases with age, 11 and its burden will double over the next generation. 12 Individuals have Parkinson's disease for approximately 14-16 years after diagnosis, 13,14 and it leads to progressive disability, cognitive impairment, limited mobility, 15 and impaired driving ability. 16 Parkinson's disease also burdens caregivers, 17 frequently requires institutional care, [18][19][20] generates high healthcare costs, 21,22 and benefits from specialty care.…”
Section: -10mentioning
confidence: 99%
“…Its incidence increases with age, 11 and its burden will double over the next generation. 12 Individuals have Parkinson's disease for approximately 14-16 years after diagnosis, 13,14 and it leads to progressive disability, cognitive impairment, limited mobility, 15 and impaired driving ability. 16 Parkinson's disease also burdens caregivers, 17 frequently requires institutional care, [18][19][20] generates high healthcare costs, 21,22 and benefits from specialty care.…”
Section: -10mentioning
confidence: 99%
“…Dementia develops in up to 60% of patients suffering from Parkinson's disease (PD) (Buter et al 2008), and importantly contributes to the impairment of the quality of life and to caregiver distress. The mechanisms of PD related dementia (PDD) are still poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…One study reported that the cumulative incidence of developing cognitive impairment was 8.5% within 1-year follow-up, and up to 47.4% within 6-year follow-up [24]. In another study, the incidence of cognitive impairment in PD patients increased to 60% by 12 years of retrospective follow-up [25]. However, cognitive decline was found to be stable in newly diagnosed patients with PD.…”
Section: Discussionmentioning
confidence: 99%